2018
DOI: 10.1002/cbdv.201700506
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Anti‐melanogenic Activities of Essential Oils from Chrysanthemum boreale Makino at Different Harvesting Stages

Abstract: In the present study, the chemical compositions and skin whitening-related antioxidant and anti-melanogenic effect of essential oils (EOs) extracted from Chrysanthemum borealeMakino (CBM) (CBMEOs) at vegetative, pre-flowering and full-flowering are investigated and contrasted among the three stages. The yields and components of the CBMEOs were different at each stage. The CBMEOs increased DPPH and ABTs scavenging activities and attenuated the α-melanocyte stimulating hormone (α-MSH)-induced tyrosinase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 51 publications
2
27
0
5
Order By: Relevance
“…In another study, it was able to eliminate about 81% of the DPPH radicals and reduce the potency of the radicals when the concentration decreased from 1.0 μ M/mL to 0.1 μ M/mL [ 38 ]. Similar data were described in the study by Kim et al, in which eugenol performed the elimination of ABTS free radicals (76.9% at a dose of 20 μ g/mL) and DPPH (90.8% at a dose of 20 μ g/mL) in L-ascorbic acid in 76.9% and 89.9%, respectively [ 14 ].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In another study, it was able to eliminate about 81% of the DPPH radicals and reduce the potency of the radicals when the concentration decreased from 1.0 μ M/mL to 0.1 μ M/mL [ 38 ]. Similar data were described in the study by Kim et al, in which eugenol performed the elimination of ABTS free radicals (76.9% at a dose of 20 μ g/mL) and DPPH (90.8% at a dose of 20 μ g/mL) in L-ascorbic acid in 76.9% and 89.9%, respectively [ 14 ].…”
Section: Resultssupporting
confidence: 84%
“…), beans [ 4 ], coffee [ 5 ], cinnamon ( Cinnamomum verum J. Presl), basil ( Ocimum basilicum L.) [ 6 ], “canelinha” ( Croton zehntneri Pax et Hoffm) [ 7 ], banana [ 8 , 9 ], bay laurel ( Laurus nobilis L.), and other foods [ 10 ]. Among the plants that contain eugenol, soybeans, cloves, beans, and cinnamon also present the antioxidant activity, possibly performed by this compound and other constituents [ 11 14 ]. In addition, clove is also known by anti-inflammatory activity [ 15 ], which may be related to anti-inflammatory action of eugenol ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It possesses potent antioxidant activities owing to its phenolic group. Measuring the antioxidant activity of eugenol using 2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-(2,4,6-trinitrophenyl) hydrazyl (DPPH) assays revealed that eugenol eliminates 76.9% and 90.8% of ABTS and DPPH free radicals, respectively [60]. The multiple free-radical scavenging testing method for five ROS (hydroxyl radical, superoxide, alkoxyl radical, peroxyl radical, and singlet oxygen) revealed a high singlet oxygen scavenging activity for eugenol [61].…”
Section: Discussionmentioning
confidence: 99%
“…Germacrene D (10.6-34.9%), β-caryophyllene (10.8%), (-)-camphor (10.8-18.0%), β-thujone (11.7%), α-thujone (9.8%) [31] Anticancer activities of EO mixtures as a whole and only a hypothetical correlation between the chemical profile and the anticancer activity have been described for some EOs. In some cases, EOs' bioactive properties were related to the anticancer activity of specific components.…”
Section: Essential Oilsmentioning
confidence: 99%
“…When referring to EOs, their chemical composition and biological activities strictly depend on habitat, climate condition, season, agronomic practices, soil type, extraction procedures, as well as the harvesting stages and storage conditions of plants [31,36,37,51,75,[97][98][99][100][101][102][103]. All these elements should be taken into account.…”
Section: Essential Oilsmentioning
confidence: 99%